Age-group identity and political participation - Samuel Trachtman; Sarah F Anzia; Charlotte Hill (Research & Politics)
In many ways, American democracy seems to work better for older citizens than younger citizens, and one explanation is that young adults vote at much lower rates than their older counterparts. Yet while the existence of the age gap in turnout is well established, there remains uncertainty as to what drives it. In this paper, we explore age as a potentially important group identity and evaluate whether strength of age-group identity predicts political participation. Adapting established measures in the social identity literature, we surveyed a representative sample of American adults to gauge how strongly they identified with others in their age group. We find that, on average, younger adults identify less strongly than senior citizens with others their age. However, for young adults, age-group identity is as strong as another form of group identity that has gotten considerable attention in the literature: political party identity. The strength of age-group identity also predicts both voting and participating in climate change protests, especially for young adults. Age-group identity is a stronger predictor of climate protest participation for young Republicans than young Democrats—suggesting there may be potential for a bipartisan coalition of young people active on the issue of climate change.